The effect of mild-stage Alzheimer’s disease on the acoustic parameters of voice - Emel Arslan-Sarımehmetoğlu; Elife Barmak (The Egyptian Journal of Otolaryngology)
Abstract Objective Our study aimed to reveal the differences by comparing the objective and subjective voice features of individuals diagnosed with mild-stage Alzheimer’s disease (AD) with those with normal cognitive abilities. Methods The study comprised 51 participants, who were divided into two groups: those with AD (study group, n = 28) and those with normal cognitive abilities (control group, n = 23). In the objective voice assessments of the participants, s/z ratio, maximum phonation time (MPT), F0, F1, F2, F3, jitter, shimmer, and NHR values were examined. The Voice Handicap Index-10 (VHI-10) and Voice-Related Quality of Life Scale (V-RQOL) were employed for the subjective assessments. Results In both males and females, the jitter and shimmer values in the study group were considerably higher than those in the control group (p < 0.000). The MPT of male participants in the study group was significantly lower than that of male participants in the control group (p < 0.036). Regarding VHI-10 and V-RQOL, the groups showed no statistically significant variation (p > 0.005). Conclusion Differences in shimmer, jitter, and MPT values based on gender among individuals with mild-stage AD indicate an impact on voice quality. It is suggested that clinicians should consider voice parameters during the assessment and intervention processes for mild-stage AD.